PEMBERDAYAAN KADER CEGAH MALNUTRISI LEWAT POSITIVE BODY IMAGE DI KELURAHAN PASIR PUTIH - Sintha Fransiske Simanungkalit; Nanang Nasrulloh; Duma Lumbantobing; Ruth M Bunga Wadu (Jurnal Abdi Insani, 2023)
Perceived body image is a person's satisfaction with the weight he has, satisfaction in appearance, body shape, evaluating appearance and orientation of appearance and attention. More than 50% of young women want a slim body and the same number of young men want a change in weight. Negative body image causes a person to do a strict diet which has an impact on nutritional status. Community service activities that aim to provide knowledge related to body image which is given through empowerment to cadres so they can prevent malnutrition. This community service activity uses the counseling method with Power Point media and leaflets. This activity was carried out from early January to November 2022. Counseling was carried out directly to cadres in Pasir Putih Village, Depok. There were 26 cadres present. In this community service activity, an evaluation of the cadres was carried out in the form of questions related to positive body image knowledge. Community service activities are effective in increasing the knowledge of cadres. The results of the evaluation of the cadres were analyzed using a paired t-test and found that there were differences in knowledge before and after counseling with a p value of 0.02. The average value before being given counseling was 74.62 and after being given counseling it increased to 82.31. This community service activity has proven to be effective in increasing the knowledge of the cadres so that it is hoped that the cadres can prevent malnutrition through a positive body image.